Kekerapan Amalan Komunikasi Kepengurusan di Kalangan Ketua-Ketua Jabatan Kerajaan di Perlis - Safinaz, Man (2003)
The purpose of this study is to examine the factors related to the frequency of practicing managerial communication among government department leaders in Perlis. The objectives of this study were to investigate the relationship between independent variables such as the content of communication message, communication nvironment, organization environment and communication channel with dependent variable (frequency of practicing managerial communication). This study involved 52 respondents which are government department leaders in Perlis. A set of questionnaire using five points Likert type scale was applied to measure the respondent responses. Four hypotheses were constructed for this study. Statistical tool such as Pearson Correlation was used to test these hypotheses. The result revealed that a) There was no significant relationship between the content of the message and the frequency of practicing managerial communication (r = 0.168, p > 0.05), b) There was no significant relationship between communication environment and the frequency of practicing managerial communication (r = 0.183, p > O.OS), c) There was no significant relationship between organization environment and the frequency of practicing managerial communication (r = 0.055, p > 0.05) and d) There was no significant relationship between communication channel and the frequency of practicing managerial communication (r =0.007, p > 0.05). Finally, this thesis attempts to offer some suggestions to enhance the effectiveness of managerial communication among government department leader in Perlis.